Impact of bimekizumab and certolizumab pegol on efficacy, safety and osteoblastic activity in radiographic axial spondyloarthritis: results from a phase IIa, multicentre, randomised, double-blind, exploratory study with PET-CT imaging - Xenofon Baraliakos; Jerney de Jongh; Denis Poddubnyy; Gerben J. C. Zwezerijnen; Robert Hemke; Sophie Glatt; Stevan Shaw; Lucian Ionescu; Assem el Baghdady; Joanne Mann; Ralph Paul Maguire; Tom Vaux; et al. (Therapeutic Advances in Musculoskeletal Disease)
Background: The efficacy and safety of bimekizumab (BKZ), an inhibitor of interleukin (IL)-17F in addition to IL-17A, has been established in axial spondyloarthritis (axSpA). Early assessment of new bone formation is possible using 18 F-fluoride positron emission tomography-computerised tomography (PET-CT) imaging to quantitatively monitor osteoblastic activity. Objectives: This exploratory study, initiated before phase IIb/III studies, assessed the efficacy and safety of BKZ in patients with radiographic (r-)axSpA and its effect on new bone formation. Design: Patients were randomised 2:1 to BKZ 160 mg every 2 weeks (Q2W; Weeks 0–10) then 320 mg Q4W (Weeks 12–44), or the reference drug: certolizumab pegol (CZP) 400 mg Q2W (Weeks 0–4), then 200 mg Q2W (Weeks 6–10), 400 mg Q4W (Weeks 12–44). Methods: Primary (Axial Spondyloarthritis Disease Activity Score (ASDAS) change from baseline (CfB)) and secondary endpoints (ASDAS-ID, ASDAS-MI) were assessed at Week 12. PET-positive axSpA lesion counts and osteoblastic activity quantification (mean SUV auc ) were performed at baseline and Weeks 12 and 48 in the sacroiliac joints and spine (PET-CT substudy; not powered to evaluate differences). Results: In total, 76 patients were randomised; 26/76 entered the PET-CT substudy. At Week 12, the mean ASDAS CfB with BKZ was −2.1 (CZP: −1.8); ASDAS-ID and ASDAS-MI were achieved by 23.9% (11/46) (CZP: 20.8% (5/24)) and 60.9% (28/46) (CZP: 45.8% (11/24)) patients. Across treatments, clinical efficacy was maintained or increased further at Week 48. In the PET-CT substudy, the total number of PET-positive axSpA lesions and mean SUV auc were substantially reduced from baseline at Week 12 with BKZ and CZP, with reductions maintained or further reduced at Week 48. Treatments were well tolerated with no new safety signals. Conclusion: Dual inhibition of IL-17A and IL-17F with BKZ resulted in improved clinical outcomes and reduced osteoblastic activity in patients with r-axSpA, suggesting the potential of BKZ to reduce disease activity and new bone formation within 12 weeks of treatment. CZP findings were consistent with previous data. No new safety signals were identified. Trial registration: ClinicalTrials.gov, NCT03215277 ( https://clinicaltrials.gov/study/NCT03215277 ).